Transformasi Display Produk dari Etalase Fisik ke Layar Digital dalam Ritel Modern - Gracia Ma; Muthia Alya Fazhira; Sarwoto Sarwoto (Digital Business Progress, 2026)
The retail landscape is undergoing a fundamental shift from physical storefront visual merchandising to digital screen displays. This study analyzes the transformation of product displays in modern retail and its impact on consumer purchasing behavior. This research integrates the 21st-century marketing management frameworks of Kotler and Keller with theories of consumer behavior, showrooming, and product specification transparency. It examines how digital interfaces substitute for sensory touch. The methodology employed a qualitative descriptive approach through a literature synthesis of recent empirical research in Indonesia. The analysis demonstrates that digital product displays achieve maximum efficacy when structured as an integrated ecosystem combining high-fidelity interactive visuals, exhaustive technical specifications, and robust brand trust mechanisms. This transformation has been shown to significantly optimize market conversion rates and operational efficiency, provided that retailers successfully mitigate the absence of physical product evaluation through structured visual evidence and credible social validation.